Data processing on a comparative evaluation of the extraction and analysis procedures for urinary phospholipid and lysophospholipid using MALDI-TOF/MS - Li, Xin; Nakayama, Kenji; Goto, Takayuki; Akamatsu, Shusuke; Shimizu, Koji; Ogawa, Osamu; Inoue, Takahiro (Data in brief, 2019)
In this dataset we provide MALDI-TOF/MS spectra for the testing and application of a quantitative method using external ionization standards (ionization STDs) for peak-intensity normalization. The presented data is related to our recent article entitled “a comparative evaluation of the extraction and analysis procedures for urinary phospholipid and lysophospholipid using MALDI-TOF/MS”. Gradient dilutions of mixture containing thirteen phospho- and lysophospho-lipid species (internal STDs) were mixed with constant concentration of the ionization STDs and analyzed together. Peak intensities of the internal and ionization STDs were picked by a homemade workflow based on OpenMS (steps including noise filtration, baseline subtraction and peak-picking). The peak-intensity ratios between the internal and ionization STDs were linearly correlated with their concentration ratios. Using this method, the evaluation of efficiencies of six different lipid extraction methods was performed in urine samples. In summary, a free and easy-to-use method for phospholipid and lysophospholipid quantitative analysis based on MALDI-TOF/MS is provided in this article.